PROS AND CONS OF GOING TO SCHOOL AT AGE 5 OR 7 - Norboyeva Azima Olim qizi; Z. Z. Salieva (TADQIQOTLAR.UZ, 2024)
ABSTRACT: This article discusses a question that many parents are wondering in today’s modern world: should I send my child to school at age 5 or 7? At the same time, a lot of information about the advantages and the disadvantages as well as main causes of these age limits is provided. One can take necessary advice who is having a hesitation with the exact time of enrolling his or her children to school.